Respon Pertumbuhan Kultur Biji Jeruk Siam Seed (Citrus nobilis var. Microcarpa) dengan Penambahan Ekstrak Tauge dan Benzilaminopurine (BAP) - Riza Linda, Irena Priscilla Corina, Mukarlina (Jurnal Protobiont, 2014)
Jeruk Siam (Citrus Nobilis var. Microcarpa) is one of the orange that become a commodity in Pontianak. The purpose of this experiment is to investigate the effects of sprout extract and BAP and the optimum conceration for the growth of Jeruk Siam culture seed orangesiam Seed. Research conducted for 3 months from June to August 2013 in the Tissue Culture Laboratory of Biology, University of Tanjungpura Pontianak. Completely Randomized Design (CRD) factorial with 2 factors treatment was used for experimental design. The first factor on the sprout extract concentration level (0 %, 5 %,10%,15 % , ) and the second factor on the level of concentration of BAP (0 ppm, 0.5 ppm , 1 ppm, 1.5 ppm) The results showed there are significant influence between sprout and extract concentration of 0.5 ppm BAP with 10 % sprout extract and 1 ppm BAP with 15 % sprout extract of 2.875 strands. The given of 10% sprout extract and number of plantlets 3.5 plantlets dry weight of 0.38 grams . BAP 0.5 ppm produce plantlets 4.988 cm tall and produces a concentration of 1 ppm wet weight of 0.2 grams.